Inclusive Memory: The Power of Collective Remembering in Gloria Naylor's The Women of Brewster Place - Sarah Foust Vinson (Limina: A Journal of Historical and Cultural Studies, 2013)
This essay considers how collective memory works to develop and sustain a group identity in Gloria Naylor's 1980 novel, The Women of Brewster Place. Using post-structural theorist Bronwyn Davies's collective biography project as a model through which to understand Naylor's work, it becomes clear how collective remembering in the novel prompts the women characters to become aware of the hegemonic forces shaping their lives.